(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Korean grammar has a unique complex structure compared to other languages, and it is especially important to study the syntactic and semantic aspects of conjunctions in depth. Conjunctions are one of the main elements that ensure the logical connection between sentences in any language system, through which the integrity and consistency of thought are ensured. Causal conjunctions are especially important in expressing cause-and-effect relationships between sentences. The principles of using causal conjunctions in Korean and their semantic analysis are a relevant topic from the point of view of linguistics.